Honesty in Accounting and Control: A Discussion of “The Effect of Information Systems on Honesty in Managerial Reporting: A Behavioral Perspective”* - Salterio, Steven E.; Webb, Alan (Contemporary Accounting Research, 2006)
Be honest to those who are honest, and be honest to those who are not honest.